Estudo das variáveis que afetam a tenacidade e a ductilidade do aço PH13-8Mo utilizado na indústria aeronáutica - Moreno, Rômulo Fernandes (2012)
Precipitation Hardening Stainless Steel PH13-8Mo is a high strength steel used in the aerospace industry. Beyond the high strength, this grade has relatively high toughness and ductility for the strength achieved. The aerospace industry is increasingly asking for high strength materials with higher toughness and ductility than the actual limits required. Villares Metals, manufacturer of specialty steels and alloys, supplies the 13-8 steel (Villares grade N4534QA) for the aerospace industry like Embraer and ELEB (landing gear manufacturer of Embraer aircrafts). Although Villares 13-8 steel meets the international and the aerospace specifications, is characteristic of this company to improve its products and follow the new requirements of the customers and the market. Thus, is of its interest to produce the 13-8 steel with higher toughness and ductility. Therefore, the objective of this work is to study the variables which affect the 13-8 steel toughness and ductility aiming to produce it with improved properties. It were studied the effect of the alloying and residual elements, steelmaking process (remelting), hot forming process (forging and rolling) and heat treatment process. The verification of these effects was verified through tensile and impact Charpy V tests.